Analysis of Lethality and High-risk Factors of Birth of Children with Congenital Heart Disease - G.S. Chaykovska; O.Z Gnateyko (Zaslavsky O.Yu., 2012)
There was carried out a retrospective analysis of 251 case reports of dead children, lethality rate from isolated congenital heart diseases of 27 newborns and 26 infants during 2006-2010. It was established that among all congenital malformations, which are 68.1 % of overall pathology, congenital heart diseases were detected in one in three cases of lethality and in one in two - in infants. Lethality of newborns with congenital heart diseases was detected in most cases among girls and children residents of cities. There were revealed some risk factors, which could be and/or were the cause of congenital heart diseases during pregnancy. Investigation of lethality rate is of great importance for early surgical treatment.